2018
DOI: 10.1093/ve/vey028
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial coinfection can promote within-host viral diversity

Abstract: In many viral infections, a large number of different genetic variants can coexist within a host, leading to more virulent infections that are better able to evolve antiviral resistance and adapt to new hosts. But how is this diversity maintained? Why do faster-growing variants not outcompete slower-growing variants, and erode this diversity? One hypothesis is if there are mutually beneficial interactions between variants, with host cells infected by multiple different viral genomes producing more, or more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 78 publications
5
35
0
1
Order By: Relevance
“…As another example, it has been shown that mutually beneficial interactions among genetically different virus strains that lead to increased viral output from the infected cell can promote coexistence, even in the presence of significant fitness differences (Leeks et al. ). Such interactions will be incorporated into our modeling framework in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As another example, it has been shown that mutually beneficial interactions among genetically different virus strains that lead to increased viral output from the infected cell can promote coexistence, even in the presence of significant fitness differences (Leeks et al. ). Such interactions will be incorporated into our modeling framework in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that frequent coinfection can have an overall deleterious effect on the virus population due to the persistence of defective or inferior virus strains, which outweighs the advantages derived from viral sex at high multiplicities (Froissart et al 2004). As another example, it has been shown that mutually beneficial interactions among genetically different virus strains that lead to increased viral output from the infected cell can promote coexistence, even in the presence of significant fitness differences (Leeks et al 2018). Such interactions will be incorporated into our modeling framework in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By allowing the same host cell to be infected by multiple viral genomes simultaneously, CIUs allow for interactions between viruses even when we would otherwise expect coinfection to be rare, such as when there are strong population bottlenecks or low ratios of infectious viral particles to susceptible host cells (McCrone & Lauring 2018;Sanjuán 2018). Interactions between viral sequences can have important consequences for viral pathogenesis, diversity, and the evolution of antiviral resistance (Bordería et al 2015; Leeks et al 2018;Tanner et al 2014;Vignuzzi et al 2006; Xue et al 2016). Furthermore, CIUs allow for repeated interactions between viral sequences, and this sets the stage for viral social adaptations.…”
Section: Introductionmentioning
confidence: 99%